DETERMINANTS OF JOB SATISFACTION - Misna Ariani; Raden Roro Hesti Mugiastuti (Jurnal Manajemen dan Kewirausahaan, 2022)
Determining the employees’ career contentment is crucial at this time. Companies should pay more attention to employee career contentment. This research focused to the determinant of employee career contentment through organizational culture, work environment, organizational commitment toward 98 office and workshop employees at PT Bukaka Teknik Utama Balikpapan Branch. It used classical assumption to test research hypothesis by analyzing feasibility with multiple linear regression model. The result revealed that organizational culture, work environment, and organizational commitment had a significative effects on employee job satisfaction. The work environment was influential but not so important. Furthermore, organizational culture had dominant effect to the employees’ job satisfaction. The work environment communication connection (communication between fellow employees), especially played role in the application of work and conformance with standard operating procedures, making it easy for employees to understand. The author realized attention of an acceptable work environment to increase the level of career contentment. The practical implications of this research results can be consideration for similar industrial companies in providing maximum satisfaction related to organizational culture, work environment, and organizational commitment. Employees satisfied at work and afforded occasions to advance themselves, if companies concerned to the availability of work facilities and convenience.